2017
DOI: 10.1021/jacs.7b07494
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Photoluminescence across the Visible Spectrum and Photocatalytic Activity of Mixed-Valence Rhenium Oxide Nanoparticles

Abstract: Materials exhibiting excitation-wavelength-dependent photoluminescence, PL, are useful in a range of biomedical and optoelectronic applications. This paper describes a nanoparticulate material whose PL is tunable across the entire visible range and is achieved without adjusting particle size, any postsynthetic doping, or surface modification. A straightforward thermal decomposition of rhenium (VII) oxide precursor yields nanoparticles that comprise Re atoms at different oxidation states. Studies of time-resolv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 31 publications
2
39
0
Order By: Relevance
“…It can be concluded that changes in the Tauc-plot indicate that the Re NPs dominates the UV-Vis spectrum. The band gap energy values obtained are also compatible with the literature [34,41,42]. It was found that the absorption spectra of Re/ReO 3 mixture and pure ReO 3 NPs were varied within the range from ultraviolet region to infrared region in spectrum depending on the synthesis parameters.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…It can be concluded that changes in the Tauc-plot indicate that the Re NPs dominates the UV-Vis spectrum. The band gap energy values obtained are also compatible with the literature [34,41,42]. It was found that the absorption spectra of Re/ReO 3 mixture and pure ReO 3 NPs were varied within the range from ultraviolet region to infrared region in spectrum depending on the synthesis parameters.…”
Section: Resultssupporting
confidence: 88%
“…XRD results of the ReO 3 NPs are shown in Figure 2 ReO 3 in literature [34]. All of the samples show semi-broad diffraction peaks and these broad peaks are due to the small size of the ReO 3 nanocrystals [35].…”
Section: Resultsmentioning
confidence: 93%
“…[1c, 3] However,itisessentially useless because of the low PL efficiencya nd poor color difference.R ecent focus of Ex-De materials has been on nanoparticles (nanocrystals and carbon/silica dots) and metal complexes. [4] Forthe former, the emission wavelength can be shifted by using size control (or size distribution), element doping, and surface states.Surface functional groups,s uch as CÀN/CÀOa nd/or CÀN, can efficiently introduce new energy levels for electron transitions and lead to the Ex-De phenomenon. [4a-c] Fort he latter, incorporating metal ions into an organic ligand, which generally facilitates intersystem crossing from the singlet to triplet states,r esulted in phosphorescence and prompt fluorescence.…”
mentioning
confidence: 99%
“…Surface functional groups, such as C−N/C−O and/or C−N, can efficiently introduce new energy levels for electron transitions and lead to the Ex‐De phenomenon. For the latter, incorporating metal ions into an organic ligand, which generally facilitates intersystem crossing from the singlet to triplet states, resulted in phosphorescence and prompt fluorescence. Purely organic materials that have the advantages of excellent processability, wide variety, good biocompatibility, and appreciable stability are attractive alternatives.…”
Section: Methodsmentioning
confidence: 99%